2017
DOI: 10.5551/jat.40717
|View full text |Cite
|
Sign up to set email alerts
|

Central Hemodynamics for Management of Arteriosclerotic Diseases

Abstract: Arteriosclerosis, particularly aortosclerosis, is the most critical risk factor associated with cardiovascular, cerebrovascular, and renal diseases. The pulsatile hemodynamics in the central aorta consists of blood pressure, flow, and stiffness and substantially differs from the peripheral hemodynamics in muscular arteries. Arteriosclerotic changes with age appear earlier in the elastic aorta, and age-dependent increases in central pulse pressure are more marked than those apparent from brachial pressure measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 158 publications
0
12
0
Order By: Relevance
“…There is a close relationship between arterial viscoelasticity and hemodynamics. Arterial stiffness can result from hemodynamic changes [16]. Blood flow acts on the vessel wall to create wall shear stress, and the vessel wall stagnates viscous blood to form a boundary layer and the particle retention.…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relationship between arterial viscoelasticity and hemodynamics. Arterial stiffness can result from hemodynamic changes [16]. Blood flow acts on the vessel wall to create wall shear stress, and the vessel wall stagnates viscous blood to form a boundary layer and the particle retention.…”
Section: Discussionmentioning
confidence: 99%
“…At least part of this relationship might be causal, involving the deleterious consequences of COPD on large-vessel arterial elasticity (i.e., aortic) and peripheral arterial conductance [41]. The former, in particular, is an important determinant of left ventricular afterload and long-term increases in myocardial O 2 demands [42]; moreover, central arterial stiffness has been considered a risk factor for the progression of atherosclerosis [37]. Although a number of previous studies have found increased arterial stiffness and impaired flow-mediated dilation in patients with COPD (including some with preserved FEV 1 ), none of these investigations selectively assessed patients with remote or absent exacerbation history and low symptom burden, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The structural arterial changes related to ageing include elastin fragmentation, collagen accumulation, vascular smooth muscle cell loss, occurrence of vascular calcium phosphate deposits in the arterial intima and media, associated with the development of the atherosclerotic plaque, and "inflammaging", a chronic low-grade inflammation that develops with advanced age [20,21]. The consequences include alterations in central haemodynamics, impaired vascular compliance, increased arterial stiffness and pulse pressure, endothelial dysfunction, hypertension, left ventricular hypertrophy, diastolic dysfunction, heart failure, as well as damage to the microvasculature in the kidney and brain [20,22,23]. Systems for the assessment of vascular alterations have been developed over the past two decades.…”
Section: Medical Devices For Vascular Ageing Assessmentmentioning
confidence: 99%
“…In particular, arterial stiffness can be assessed by local distensibility and using carotid to femoral, brachial-ankle or heart-ankle pulse wave velocity (PVW), and aortic waveform-derived indices, such as augmentation index, endothelial dysfunction by flow-mediated dilation of the brachial artery, subclinical atherosclerosis by intima-media thickness, the atherosclerotic plaque by vascular ultrasound and magnetic resonance imaging, and coronary artery calcifications by computed tomography [20,24]. Central blood pressure can be measured invasively by inserting an intra-arterial catheter connected to a pressure transducer, or estimated noninvasively from carotid blood pressure waveform, or from radial blood pressure through mathematical conversion [23]. Medical devices available on the market for the above-mentioned vascular ageing parameters include (Figure 3): i) Medical imaging based on ultrasound, magnetic resonance imaging, computed tomography/positron emission tomography (MRI, CT/PET) machines; ii) Sensor based non-invasive systems such as tonometry, oscillometry, photoplethysmography, sphygmomanometry; iii) Intravascular based systems such as catheters for plaque assessment (intravascular ultrasound, optical coherence tomography) or haemodynamic analysis (pressure wire, Doppler wire, absolute flow wire); iv) Software for image and data processing; software can be part of the above-mentioned techniques or can be a stand-alone system working independently of the hardware for data acquisition (i.e.…”
Section: Medical Devices For Vascular Ageing Assessmentmentioning
confidence: 99%